A study of mobile IP and its security aspects in a LAN environment / Suhaila Che Ismail - Che Ismail, Suhaila (1998)
Mobility, is the ability of a node to change its poinf-of-attachment from one link to another, maintaining all existing communications and using the same IP address at its new link. This is a new solution meant for a mobile node that might be utilising applications that may not be interrupted when the mobile node moves from one link to another. Mobility allows mobile node to communicate even distances away without restarting any applications in use. The mobile IP involves two-part solution comprising the Mobile IP Agents and the Mobile Nodes. When a user needs to use the mobile IP, the home agent and security information are selected. Security is a pertinent aspect of the mobile IP architecture. Every time a mobile node moves and attempts to register with its home agent, an authentication scheme is implemented to verify the identity of the mobile nodes. The algorithm consideration is sine qua non in setting-up the whole network system allowing the mobile devices to move freely among sub-networks. A security criteria, outlines the authentication algorithm and key to be used during the registration process. Each mobile IP agent needs a different application and independently configured. Therefore, a thorough research is to be accomplished in order to produce the mobile IP to the extent of the security features and the algorithm.